Ascospore Infection and Colletotrichum Species Causing Glomerella Leaf Spot of Apple in Uruguay - Alaniz, Sandra (Plant Pathol J, 2019)
Glomerella leaf spot (GLS) caused by Colletotrichum spp. is a destructive disease of apple restricted to a few regions worldwide. The distribution and evolution of GLS symptoms were observed for two years in Uruguay. The recurrent ascopore production on leaves and the widespread randomized distribution of symptoms throughout trees and orchard, suggest that ascospores play an important role in the disease dispersion. The ability of ascospores to produce typical GLS symptom was demonstrated by artificial inoculation. Colletotrichum strains causing GLS did not result in rot development, despite remaining alive in fruit lesions. Based on phylogenetic analysis of actin, β-tubulin and glyceraldehyde-3-phosphate dehydrogenase gene regions of 46 isolates, 25 from fruits and 21 from leaves, C. karstii was identified for the first time causing GLS in Uruguay and C. fructicola was found to be the most frequent (89%) and aggressive species. The higher aggressiveness of C. fructicola and its ability on to produce abundant fertile perithecia could help to explain the predominance of this species in the field.